Magnetomotive Displacement of Magnetic Nanoparticles in Different Tissue Phantoms - Huber, Christian; Heim, Christian; Li, Jiaqi; Ermert, Helmut; Rupitsch, Stefan J.; Ullmann, Ingrid; Lyer, Stefan (Current Directions in Biomedical Engineering, 2024)
Magnetic nanoparticles (MNPs) can be used invarious biomedical applications, such as magnetic drug tar-geting (MDT) or magnetic hyperthermia for cancer treatment.MNPs are injected into the body and accumulated with anexternal magnetic field at the tumor site. For therapy mon-itoring, the MNPs distribution has to be accurately mappedin real time. Magnetomotive ultrasound (MMUS) is a suit-able technique for this purpose. It was already demonstratedthat MMUS can map the accumulation process of MNPs dur-ing MDT. Moreover, inverse MMUS is an advanced techniqueto quantify MNP distribution. This method simulates the dis-placement of MNPs and surrounding tissues and compares theresults to measured data. Understanding how magnetomotivedisplacement behaves in various elastic environments is cru-cial for advancing inverse MMUS and accurately quantifyingMNP distributions. In this study, ultrasound tissue phantomswere fabricated with varying elastic parameters, incorporatingMNPs. Subsequently, their MMUS displacement is assesse
Keywords: Ultrasound Imaging; Displacement Tracking; Magnetic Nanoparticles; Magnetic Drug Targeting